Genetic mapping of QTLs for drought tolerance in chickpea (Cicer arietinum L.) - Kushwah, Ashutosh; Bhatia, Dharminder; Barmukh, Rutwik; Singh, Inderjit; Singh, Gurpreet; Bindra, Shayla; Vij, Suruchi; Chellapilla, Bharadwaj; Pratap, Aditya; Roorkiwal, Manish; Kumar, Shiv; Varshney, Rajeev K.; et al. (Frontiers in Genetics, 2022)
Chickpea yield is severely affected by drought stress, which is a complex quantitative trait regulated by multiple small effect genes. Identifying genomic regions associated with drought tolerance component traits may increase our understanding of drought tolerance mechanisms and assist in the development of drought tolerant varieties. Here, a total of 187 F8 recombinant inbred lines (RILs) developed from an inter-specific cross between drought tolerant genotype GPF 2 (Cicer arietinum) and drought sensitive accession ILWC 292 (C. reticulatum) were evaluated to identify quantitative trait loci (QTLs) associated with drought tolerance component traits. A total of 21 traits, including 12 morpho-physiological traits and nine root-related traits, were studied under rainfed and irrigated conditions. Composite interval mapping identified 31 QTLs at Ludhiana and 23 QTLs at Faridkot locations for morphological and physiological traits, and seven QTLs for root-related traits. QTL analysis identified eight consensus QTLs for six traits and five QTL clusters containing QTLs for multiple traits on linkage groups CaLG04 and CaLG06. The identified major QTLs and genomic regions associated with drought tolerance component traits can be introgressed into elite cultivars using genomics-assisted breeding to enhance drought tolerance in chickpea.